2023
DOI: 10.1136/bmjopen-2022-070639
|View full text |Cite
|
Sign up to set email alerts
|

Reporting quality of abstracts from randomised controlled trials published in leading critical care nursing journals: a methodological quality review

Abstract: ObjectivesTo evaluate the methodological quality of randomised controlled trial (RCT) abstracts in leading critical care nursing journals against the Consolidated Standards of Reporting Trials-Abstracts (CONSORT-A) checklist and to identify variables related with abstract reporting quality.DesignDescriptive methodological quality review.Data sourceWe searched the PubMed database and the websites of each included journal.Eligibility criteriaWe included RCT abstracts published between 2011 and 2021 in the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Moreover, a statistically significant higher overall quality score was observed in studies published in the pre-CONSORT period. Our findings align with prior studies indicating suboptimal adherence to the CONSORT guidelines for abstracts across various journals and medical disciplines, including dermatology and plastic surgery [21][22][23][24][25]28,29,34,36,37]. The purpose of adopting the CONSORT guidelines was to improve the quality of reporting, as it is necessary for the detailed translation of study results to clinicians' daily work.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, a statistically significant higher overall quality score was observed in studies published in the pre-CONSORT period. Our findings align with prior studies indicating suboptimal adherence to the CONSORT guidelines for abstracts across various journals and medical disciplines, including dermatology and plastic surgery [21][22][23][24][25]28,29,34,36,37]. The purpose of adopting the CONSORT guidelines was to improve the quality of reporting, as it is necessary for the detailed translation of study results to clinicians' daily work.…”
Section: Discussionsupporting
confidence: 83%
“…Abstracts play a significant role in the reporting of RCTs. They serve as a concise summary, containing essential study information that enables readers to quickly evaluate the study's originality, methodology, and results [21]. As the first section often read in a publication, the abstract significantly influences the readers' decision to proceed with reading further [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as we are aware, the topic of this review has not been reviewed in other medical areas by pairing full-text manuscripts and abstract-only reports. However, there have been other studies and reviews which have assessed the use of abstracts and abstract-only reports and their adherence to reporting standards and peer review, and have found them suboptimal5–9 17–20 A recent review on trustworthiness assessment for SRs found that 25% or RCTs included in 18 Cochrane SRs should not have been included in the reviews, due to issues around research governance, study feasibility and the plausibility of the results and reported baseline characteristics 21. The authors propose a formal trustworthiness assessment as part of the screening process and an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%